Hemozoin: the future in malaria diagnosis - Baptista, Vitória Cunha (2020)
Work supported by project NORTE-01-0145-FEDER-028178, funded by NORTE 2020 Portugal Regional Operational Programme, under the PORTUGAL 2020 Partnership Agreement, through the European Regional Development Fund and by Fundação para a Ciência e Tecnologia (FCT).